PROBLEMA GURU YANG MENGAJAR DI KELAS ANAKNYA DI SDN 020 RAMBAH HILIR KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Roni Saputra; Titi Maemunaty; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this study is how is the Problem Of Teachers Teaching In Their Children Class SDN 020 Rambah Hilir Rambah Hilir District Rokan Hulu Regency. In accordance with the formulation of the problem the purpose of this study was to determine the problem of teacher who teach in their children calsses at SDN 020 Rambah Hilir Rambah Hilir District Rokan Hulu Regency. This type of research is a naturalistic desriptive qualitive approach. This study consists of one vqariable, namely the Problem Of teacher who teach in their children class at SDN 020 Rambah Hilir District Rokan Hulu Regency with indicators (1) Attention, (2) Activities, (3) Appearance, (4) Demonstration, (5) Repetion, (6) Correlation, (7) Concertration, (8) Socialiization, (9) Individualization and (10) Evalution. The subjects of this study were 4 people consisting of 1 observer informant, 2 core informant and 1 control informant. Data collection teachniques used are observation. Based on the results of interviews with informants, the researchers found that through 10 indicators in this study that thw problem of teacher teaching in their children class at SDN 020 rambah hilir rambah hilir disctrict rokan hulu regency was not good. Where the teacher gave attention to studens is teaching and learning activities. The teacher gives more attention to her child in class. Furthermore, seen from the activities of student teachers who teach in their children's classrooms, these students do not participate in teaching and learning activities in class. Furthermore, it is seen from the perception of teachers who teach in their children's classrooms rarely linking knowledge with the experiences students can get in teaching and learning activities in class. Furthermore, seen from the correlation not all students can understand and understand the lesson because it depends on the ability and understanding of the student. And then it can be seen from the evaluation of teachers in teaching and learning activities in class not all of them know the progress and development of learning in classKey Words: Problem, Teachers Teaching In Their Children Class